Developing correlative Optical-Photoacustic microscopy for high-resolution in vivo imaging - Tcarenkova, Elena (fi=Turun yliopisto|en=University of Turku|, 2015)
PhotoAcoustic Imaging (PAI) is a branch in clinical and pre-clinical imaging, that refers to the techniques mapping acoustic signals caused by the absorption of the short laser pulse. This conversion of electromagnetic energy of the light to the mechanical (acoustic) energy is usually called photoacoustic eﬀect. PAI, by combining optical excitation with acoustical detection, is able to preserve the diﬀraction limited spatial resolution. At the same time, the penetration depth is extended beyond the diﬀusive limit. The Laser-Scanning PhotoAcoustic Microscope system (LS-PAM) has been developed, that oﬀers the axial resolution of 7.75 µm with the lateral resolution better than 10 µm. The ﬁrst in vivo imaging experiments were carried out. Thus, in vivo label-free imaging of the mouse ear was performed. The principle possibility to image vessels located in deep layers of the mouse skin was shown. As well as that, a gold printing sample, vasculature of the Chick Chorioallantoic Membrane Assay, Drosophila larvae were imaged by PAI. During the experimental work, a totally new application of PAM was found, in which the acoustic waves, generated by incident light can be used for further imaging of another sample. In order to enhance the performance of the presented system two main recommendation can be oﬀered. First, the current system should be transformed into reﬂection-mode setup system. Second, a more powerful source of light with the suﬃcient repetition rate should be introduced into the system.